Effects of basal medium and plant growth regulator regimes on meristem and nodal cultures in white yam (D. rotundata) - Ajayi, A.; Balogun, M.; Maroya, N.; Asiedu, Robert (International Institute of Tropical Agriculture, 2017)
Yam production is constrained by the limited availability and high cost of quality seed due to its slow vegetative propagation ratio. Micropropagation using nodal and meristem explants have been used to produce clean plantlets, with a 1:4 multiplication ratio for nodal explants and 1:1 ratio for meristem explants, the latter taking 6 to 24 months before plantlet regeneration. The effect of six hormone-free basal medium compositions, made of Murashige and Skoog (MS) medium and Gamborg’s B5 medium modified mainly in terms of nitrate to ammonium ratio on micropropagation ratio of four genotypes of white yam were investigated using single nodes from in vitro established plantlets. A second experiment was conducted on the effect of different concentrations of NAA (naphthalene acetic acid), GA3 (Gibberellic acid), BAP (benzyl amino-purine), and UP (Uniconazole-p) at different combinations on micropropagation, using a completely randomized design with 20 replicates. Data were collected on number of nodes per plantlet every four weeks for twelve weeks. ANOVA was done and means were separated at P = 0.05. The average number of nodes per plantlet after 12 weeks was 3.76 in conventional MS medium which was the best for all the genotypes except TDr 95/19177 in which there were no significant differences among the different nitrogen regimes. The B5 medium produced the lowest number of 1.85 nodes after 12 weeks of culture. Nitrogen use efficiency seems to differ among genotypes, necessitating the use of an ion-specific nutrient test for increased optimization. Medium containing 0.2 mg/l BAP and 0.1 g/l UP in MS medium produced the highest mean number of nodes (6.5) after 12 weeks. Both mineral nutrition and hormones were effective in increasing the yam micropropagation ratio.